Alcohol-Associated Liver Disease Mortality Increased From 2017 to 2020 and Accelerated During the COVID-19 Pandemic - Deutsch-Link, Sasha; Jiang, Yue; Peery, Anne F.; Barritt, Alfred S.; Bataller, Ramon; Moon, Andrew M. (Clinical gastroenterology and hepatology, 2022)
Alcohol consumption has risen substantially in the United States in the past 2 decades.1,2 Alcohol-associated liver disease (ALD) represents a greater inpatient financial burden than all other etiologies of cirrhosis combined3 and is now the leading indication for liver transplantation.4 A recent study reported that ALD mortality increased between 2006 and 2017.5 Since 2017, alcohol consumption has continued to rise, and more significantly during the COVID-19 pandemic.2 The aim of this research letter is to provide the most updated trends in ALD-related mortality in the United States and to quantify the rate of change of ALD-related mortality over time.